Laboratory production of cattle embryos [ - Gordon, Ian , 1928- (Wallingford, Oxfordshire, UK : CABI, 2003)
This new edition reviews advances in embryo production technology, based on some 3500 reports that have appeared since the first edition was published in 1994. The work emphasizes the common ground between those working in cattle and human embryology.
1. Developments in embryo in vitro production (IVP) technology -- 2. The bovine oestrous cycle and associated events -- 3. Recovering the bovine oocyte -- 4. Maturing the oocyte -- 5. Capacitating bovine sperm -- 6. In vitro fertilization -- 7. Culturin and evaluating the early bovine embryo -- 8. Preservation of embryos and oocytes -- 9. Establishing pregnancies with IVP embryos -- 10. Embryos and oocytes in research and commerce
Includes bibliographical references (396-535) and index
Keywords: Livestock -- Embryos; Livestock -- Embryos -- Transplantation